ANALISIS EVALUASI PEMBELAJARAN MATEMATIKA DAN ILMU PENGETAHUAN ALAM (MIPA) DI SMP NEGERI 1 SITURAJA KABUPATEN SUMEDANG - Wartini, Nani; Prasetyono, Hendro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the need to improve the quality of learning evaluation in Mathematics and Natural Sciences (MIPA), particularly in achieving a balanced assessment across cognitive, affective, and psychomotor domains. The purpose of this study is to analyze the implementation of learning evaluation, including planning, execution, results, and follow-up actions at SMP Negeri 1 Situraja, Sumedang Regency. This research employs a qualitative approach with a descriptive field research design. Data were collected through observation, interviews, and documentation, and analyzed using inductive and deductive techniques. The findings reveal that the evaluation planning has been systematically developed and aligned with learning objectives. However, the implementation has not been fully optimal, as the assessment tends to focus more on the cognitive domain, while the affective and psychomotor aspects are not adequately measured and are not fully integrated into the final evaluation results. Despite these limitations, the overall learning outcomes indicate that most students have achieved the minimum competency standards. Therefore, it is necessary to develop a more comprehensive, balanced, and continuous evaluation system to better represent students' overall competencies and improve the quality of the learning process.